Manuscripts of the Latin Classics 800-1200 - Kwakkel, Erik, 1970- (Studies in medieval and Renaissance book culture., 2016)
This book brings together six expert contributors to examine the production and use of medieval manuscripts containing classical Latin texts. The contributors consider everything from the physical qualities of the manuscripts to what we can learn about how their readers used and interacted with them; ultimately, they also make a case for the value of studying not just specific classical manuscripts, but distinct groups of them, showing how such a collective approach can add to our understanding of how they functioned in medieval society.